PERSEPSI MANAJER TERHADAP PUTUSAN PEMBATALAN AKAD MURABAHAH DAN FUNGSI DEWAN PENGAWAS SYARIAH - Edi Darmawijaya; Faisal Fauzan (Universitas Islam Negeri Ar-Raniry, 2018)
The inadequacy of the contract principle is included in the category of non-fulfillment of objective conditions, therefore with this opinion financing has been null and void by law. In the context of sharia this is not very good because it has consequences which are incompatible with the rules in religion. The Government has regulated through Bank Indonesia Regulation No.7 / 35 / PBI / 2005 dated September 29, 2005 concerning Commercial Banks conducting business activities based on Sharia Principles that regulate the Duties, Authorities and Responsibilities of the Sharia Supervisory Board (DPS), among others in the first point ensure and supervise the suitability of the Bank's operational activities against the fatwa stipulated by the DSN-MUI. Cases of contract cancellations have occurred, one of which at the Bukit Tinggi Court shows the control of the passive Sharia Supervisory Board (DPS). This study aims to determine the perceptions of Islamic bank managers on the decision to cancelation of financing contracts, especially murabahah and the function or role of the Sharia Supervisory Board of the Islamic bank. The Manager's perception of the cancellation of the murabahah financing contract by the Religious Court is very good and the Perception Manager of the Sharia Supervisory Board regarding the function of financing supervision in sharia banking is good.